Crack: the beginning of the stone in Brazil - Caravaca Morera, Jaime Alonso (2014)
The drug consumption has been present in the society since the beginning. The crack is considered a destructive drug, given its radical effects on the physical and emotional health and because become the consumer into a slave to their own addiction. The simplicity of the design, the exciting effects and its low cost are variables that have historically contributed to its expansion since late eighties. This article is aim at presenting a literature review of the beginning and evolution of the crack and its consequently insertion inside the Brazilian society. Nowadays has been well identified and described a profile of the crack user, however it is evident that this drug does not discriminate between sex, race, religion or social class. The public policies should ensure the implementation of actions aimed at treating and preventing drug consumption, the social reinsertion and promoting strategies of stigma/harm reduction.